The Use Of Prepositions In The Business Column Of The Jakarta Post - Hendri Hendri (Pedagogik: Jurnal Pendidikan, 2016)
This study tries to find out the use and the kinds of prepositions in the Business columns of The Jakarta Post. The problems of the prepositions are the four kinds of prepositions as Wishon and Burks (1995: 288) say, they are: simple, compound, participial and phrasal prepositions. The data of this research are the Business column of The Jakarta Post, which is taken eight editions on the first and second week, namely: 1st Wednesday, 2nd Thursday, 3rd Friday, 4th Saturday, 6th Monday, 7th Tuesday, 8th Wednesday and 9th Thursday of March 2015 After analyzing all the data obtained, some conclusions can be drawn as follows: 1)Prepositions are appeared in each edition of the Business columns of The Jakarta Post newspaper.2)The kinds of preposition that are used in the Business columns are:Simple preposition, Compound Preposition, Participial Preposition and Phrasal Preposition.3)Simple preposition is the most dominant preposition that is used in the Business columns of The Jakarta Post in each edition that is 88.30 %.